Policy Influences on Economic Growth in OECD Countries An Evaluation of the Evidence - Ahn, Sanghoon (OECD Publishing, 2000)
This paper examines the recent literature on economic growth with a focus on policy issues and evidence relevant to OECD countries. The review begins with an overview of developments in the theory of economic growth and also comments generally on the nature of evidence exploring the influences on growth. This is followed by an examination of issues relating to the link between growth and factors of production (physical and human capital). The third section of the paper assesses the evidence linking a number of other factors (or 'framework conditions') to growth, namely: macroeconomic policy; finance; trade and competition policy; 'social capital'; and, population and health issues ...
Keywords: Economics